Evaluasi Sistem Pengendalian Internal Pengeluaran Kas pada Dinas Sosial Daerah Provinsi Sulawesi Utara - Manikome, Elis Felisya; Budiarso, Novi Swandari; Afandi, Dhullo (Yayasan Widyantara Nawasena Raharja, 2025)
The implementation of the Government Internal Control System in terms of cash expenditure is important, because it aims to avoid all forms of fraud, abuse, embezzlement, and waste of state assets against cash, and to correct any errors and irregularities that occur, and can take corrective action if there are irregularities that indicate weaknesses in these internal controls. In addition to implementing the Government Internal Control System, an evaluation is also needed to assess whether the application is in accordance with applicable regulations, and whether it has been carried out optimally. This study aims to evaluate the implementation of the Internal Control System, especially the cash expenditure control activities carried out by the Regional Social Service of North Sulawesi Province. The analysis method used is descriptive qualitative. The results showed that cash expenditure control activities at the Regional Social Service of North Sulawesi Province were in accordance with the elements of control activities in PP No. 60 of 2008, but not maximised in the elements of restricting access to resources and recording them.